(The Effect Of Heat Application in Producing VCO and the Efficacy of Resulted VCO in Reducing Blood Glucose of Diabetes Mellitus Rat of Sprague Dawley) - Supriatna, Dadang; Astawan, Made; Muchtadi, Deddy (Warta Industri Hasil Pertanian, 2008)
Virgin Covonut Oil (VCO) used toÂ  be produced with various methods and each methods claims ait advantege especially in its lauric acid content. The objective of this research was to study the effect of heat application in producing VCO and the efficacy of result VCO in reducing blood glucose of diabetes mellitus (DM) rat of sprague Dawley. Three types of samples were used in the study, i.e., (1) VCO produced without heat application and (2) VCO producd with controlled heat application and (3) Ordinary coconut cooking oil produced with the application of severe heating as well as typical chemical tretment. Each sample was introduced orally to each group consisting of 5 rats. Other two groups consisting of 5 rats were also used as control, i.e., (1) negative control was of healty rat and (2) positive control was of DM rats. The animal study was conduced for 28 days and the observation was carried out on the amount of feed consumed, body weight and blood glucose. At the end of observation, all the rats were terminated and analysis was carried out on blood chorestrol level. This study revealed no significant different between VCO and Coconut Cooking Oil in body weight gain effect. The content of bioactive conpound of Lauric Acid in two types of VCO and Coconut Cooking Oil were also not significantly different. However, the VCO produced without heating showed the most significant effect in reducing blood glucose (corellation value of-0,99 and significant value at a a=1%). All the VCO samples were also not significant in affecting the level of total cholestrol, HDL, LDL, and triglyceide of blood serum of DM rat.